Rare earth elements recovery from end-of-life NdFeB magnets towards new applications using design of experiments for leaching process - Ana Paula Silva; Óscar Barros; Pier Parpot; Isabel C. Neves; Teresa Tavares; José Pinheiro-Torres; Bruna Silva (Minerals Engineering, 2026)

Integrated glycerol biorefinery: volatile fatty acid platform for polyhydroxyalkanoates production under feast/famine operation - Agnes Adam Duarte Pinheiro; Edilberto Mariano da Silva; Bruna Scandolara Magnus; Federico Battista; Lourdinha Florencio; Wanderli Rogério Moreira Leite (Bioresource Technology, 2026)

Development of citrinin-loaded liposomes and in vitro toxicogenetic evaluation on breast cells - Ag-Anne Pereira Melo de Menezes; Maria Luísa Lima Barreto do Nascimento; Antonielly Campinho dos Reis; Michely Laiany Vieira Moura; Taline Alves Nobre; Athanara Alves de Sousa; Jorddam Almondes Martins; Sérgio Eduardo Matos Cazarotti Francisco; João Pedro Alves Damaceno do Lago; Igor Gabriel Barbosa de Sousa; Helber Alves Negreiros; Marjorie Pereira Gualter; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study aimed to synthesize a liposomal nanoformulation containing citrinin (LP-CIT) to improve its availability and to evaluate its toxicogenomic profile, focusing on cytotoxic and genotoxic effects in breast cancer (MDA-MB-231) and non-tumorigenic mammary epithelial (MCF-10A) cell lines. The formulation was characterized by macroscopic appearance, pH, particle size, polydispersity index (PDI), zeta potential, encapsulation efficiency, and estability of nanoparticles. Citrinin content, encapsulation efficiency, and liposome stability were evaluated. Cytotoxicity was assessed using MTT, trypan blue exclusion, and flow cytometry. Cell death mechanisms were investigated by mitochondrial membrane potential analysis and expression of apoptotic markers (caspase-9 and BAX). Genotoxicity was evaluated using the comet assay. The liposomal nanosystem consisted of small unilamellar vesicles with a mean diameter of 143.3 nm, a PDI of 0.3, and a positive surface charge (+ 28.5 mV). The average was 63.69 ± 0.18% of citrinin encapsulated in liposomes with stability more than 21 days. Both free citrinin (CIT) and LP-CIT showed cytotoxic effects in MDA-MB-231 and MCF-10A cells, with lower LC₅₀ values observed for LP-CIT. Although LP-CIT induced more pronounced cytotoxic and genotoxic effects in the cancer cell line, toxic effects were also observed in non-tumorigenic cells, indicating limited selectivity. Cell death was associated with mitochondrial membrane depolarization and increased caspase-9 and BAX expression. Both formulations induced DNA damage as detected by the comet assay. Liposomal encapsulation enhanced citrinin biological activity but did not indicate tumor selectivity. Thus, this study represents a toxicogenomic assessment of citrinin and its liposomal formulation for potential therapeutic applicability.

Exploring the Probiotic and Antimicrobial Potential of Pediococcus Pentosaceus Isolates from Fish: Genomic and Functional Perspectives - Elionio Galvão Frota; Taís Mayumi Kuniyoshi; Mauro de Medeiros Oliveira; Pamela Oliveira de Souza de Azevedo; Taciana Freire de Oliveira; Luara Lucena Cassiano; Amanda Romana Santos Pessoa; Fernando Moises Mamani Sanca; João Victor dos Anjos Almeida; Meriellen Dias; Bruna Souza da Silva; Nathalia Vieira Porphirio Veríssimo; et al. (Probiotics and Antimicrobial Proteins, 2026)

Ruminally unprotected guanidinoacetic acid supply in sheep diets is effective in improving oocyte quality through mitochondrial function and by modulating regulatory gene markers that encode follicular growth, estrogen synthesis, and antiapoptotic activity - Jhennyfe Nobre de Sena; Camila Muniz Cavalcanti; Alfredo José Herrera Conde; Bruna Vitória de Freitas Alves; Larissa Fernandes Baia Cesar; Marta da Costa Sousa; Yohana Huicho Miguel; Louhanna Pinheiro Rodrigues Teixeira; Fernando Felipe da Silva Pereira; Gildas Mbemya Tetaping; Juliana Paula Martins Alves; César Carneiro Linhares Fernandes; et al. (Animal Reproduction Science, 2026)

Plant sources and fermentation in cellular agriculture and alternative Proteins: A review - Diean Fabiano Alvares Pinheiro; Bibiana Porto da Silva; Bruna Silva de Farias; Débora Pez Jaeschke; Janaína Oliveira Gonçalves; Pedro Minasi Brandão; Luiz Antonio de Almeida Pinto; Anelise Christ-Ribeiro (Trends in Food Science & Technology, 2026)

Copper/zinc ratio and erythrocyte superoxide dismutase in patients with thyroid nodules - Bruna Aparecida Melo Batista; Matheus Aragão Dias Firmino; Paula Alexandre de Freitas; Morgana Pinheiro Sousa; Ana Carolina Marinho Ferreira; André Pires Cortez; Wladiana Oliveira Matos; Francisco Luan Fonsêca da Silva; Carla Soraya Costa Maia (BioMetals, 2025)

Detection of Sporothrix brasiliensis in Human Tissue by Direct PCR Using Species-Specific Primers and NESTED PCR in a New Epidemic Area of Sporotrichosis - Jucieli Firmino de Freitas; Giselle da Silva Barbosa; Raul Leal Faria Luiz; Cláudia Elise Ferraz; Bruna Rodrigues de Sousa; Cicero Pinheiro Inácio; Armando Marsden Lacerda Filho; Rejane Pereira Neves; Manoel Marques Evangelista Oliveira; Reginaldo Gonçalves de Lima-Neto (Mycopathologia, 2025)

Hydraulic and climate controls of hypogene and epigene speleogenesis at a regional scale in northeastern Brazil - Augusto S. Auler; Philippe Audra; Jo De Waele; Rubson P. Maia; Francisco H.R. Bezerra; Xianfeng Wang; Marco Antonellini; Fabrizio Balsamo; Giovanni Bertotti; Carla Furtado; Vincenzo La Bruna; Rebeca Lima; et al. (Geomorphology, 2025)

Pollination of endangered Philodendron cipoense (Araceae): floral scent ensures the attraction of several specialized cyclocephaline beetle species (Melolonthidae, Cyclocephalini) - Bruna Karen Pinheiro-Costa; Artur Campos Dália Maia; Reisla Oliveira; Paschoal Coelho Grossi; Stefan Dötterl; Clemens Schlindwein (Arthropod-Plant Interactions, 2025)

Cover crops enhance soil health, crop yield and resilience of tropical agroecosystem - Victória Santos Souza; Lucas Pecci Canisares; Bruna Emanuele Schiebelbein; Darliane de Castro Santos; Rafael Braghieri Menillo; C. Roberto Pinheiro Junior; Maurício Roberto Cherubin (Field Crops Research, 2025)

DiverReef : A global database of the behavior of recreational divers and their interactions with reefs over 20 years - Vinicius J. Giglio; Johnatas Adelir‐Alves; Natalia Balzaretti Merino; Myrna Leticia Bravo‐Olivas; Emma F. Camp; Edoardo Casoli; Rosa Maria Chávez‐Dagostino; Eliana Ferretti; Douglas Fraser; Ana C. Grillo; Santiago Jiménez‐Guiérrez; Kelen L. Leite; et al. (Ecology, 2025)
Recreational diving is an important activity in reef environments worldwide, providing income and employment for coastal communities and connecting visiting divers to these ecosystems promoting conservation and stewardship. However, if poorly managed, diving has the potential to cause detrimental effects on benthic communities via mechanical damage caused by physical contact of divers with the reef, often in the form of unintentional fin kicks resulting from poor buoyancy. Understanding diver–reef interaction patterns is important to elucidate the potential impacts of diving tourism on the reef biota. The DiverReef database provides the first public dataset on the underwater behavior of recreational divers in shallow reef environments (

Pollonein-LAAO unveiling anti-angiogenic effects through oxidative stress: Insights from mimetic tumor angiogenesis environment in a 3D co-culture model - Lorena Polloni; Tássia Rafaella Costa; Lorena Pinheiro Morais; Bruna Cristina Borges; Samuel Cota Teixeira; Thales Alves de Melo Fernandes; Lucas Ian Veloso Correia; Luciana Machado Bastos; Andreimar Martins Soares; Marcelo José Barbosa Silva; Eloisa Amália Vieira Ferro; Daiana Silva Lopes; et al. (Chemico-Biological Interactions, 2025)

Synergistic antifungal effect of thiophene derivative as an inhibitor of fluconazole-resistant Candida spp. biofilms - Adryelle Idalina da Silva Alves; Bruna Rodrigues de Sousa; Janderson Weydson Lopes Menezes da Silva; Dyana Leal Veras; Fábio André Brayner; Luiz Carlos Alves; Francisco Jaime Bezerra Mendonça Junior; Cicero Pinheiro Inácio; Rejane Pereira Neves (Brazilian Journal of Microbiology, 2024)

Chitosan Gel as a Fat Substitute in Tambaqui Fish Burger - Bruna Pinheiro Santos; Valfredo Figueira da Silva; Maria Ildilene da Silva; Adriana Sathie Ozaki Hirata; Marcio Douglas Goes; Maria Luiza Rodrigues de Souza; Elenice Souza dos Reis Goes (Journal of Aquatic Food Product Technology, 2024)

Homogeneity analysis of daily precipitation series in Paraná State, Southern Brazil - André Rodrigues da Silva; Bruna Forestieri Bolonhez; Hemerson Donizete Pinheiro (Theoretical and Applied Climatology, 2024)

Caffeine Consumption and Interaction with ADORA2A, CYP1A2 and NOS1 Variants Do Not Influence Age at Onset of Machado-Joseph Disease - Ana Carolina Martins; Jordânia dos Santos Pinheiro; Luciana Szinwelski; Eduardo Rockenbach Cidade; Danilo Fernando Santin; Laura Damke Proença; Bruna Almeida Araújo; Maria Luiza Saraiva-Pereira; Laura Bannach Jardim (The Cerebellum, 2024)

Volatile fatty acid and methane production from vinasse and microalgae using two-stage anaerobic co-digestion - Agnes Adam Duarte Pinheiro; Edilberto Mariano da Silva; Dicla Cesario Pereira de Oliveira; Bruna Scandolara Magnus; Fabrício Motteran; Lourdinha Florencio; Wanderli Rogério Moreira Leite (Environmental Science and Pollution Research, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Comment on “No wild bees? Don't worry! Non-bee flower visitors are still hard at work: The edge effect, landscape, and local characteristics determine taxonomic and functional diversity in apple orchards” [Agric. Ecosyst. Environ. 345 (2023) 108554] - José N. Mesquita-Neto; Victor Hugo Monzón; Rodrigo de O. Araujo; Bruna K. Pinheiro-Costa; Benito Cortés-Rivas; Laura C. Pérez-Giraldo; Catalina Escanilla-Jaramillo; Sharon Rodríguez (Agriculture, Ecosystems & Environment, 2024)

Does chronic nitrogen deposition have effects on grass physiology of natural habitats? - Ana Maria Ferreira; Ana Paula Faria; Heraldo L. Vasconcelos; Emilio M. Bruna; Vladimir Eliodoro Costa; Ana Silvia Franco Pinheiro Moreira (South African Journal of Botany, 2024)

An ex vitro hairy root system from petioles of detached soybean leaves for in planta screening of target genes and CRISPR strategies associated with nematode bioassays - Nayara S. Freitas-Alves; Clidia E. Moreira-Pinto; Fabrício B. M. Arraes; Lorena S. de L. Costa; Rayane A. de Abreu; Valdeir J. V. Moreira; Isabela T. Lourenço-Tessutti; Daniele H. Pinheiro; Maria E. Lisei-de-Sa; Bruno Paes-de-Melo; Bruna M. Pereira; Patricia M. Guimaraes; et al. (Planta, 2024)

Chemical and ecotoxicological indicators for evaluating the treatment of coal mining wastes - Zuleica Carmen Castilhos; Ricardo Gonçalves Cesar; Silvia Gonçalves Egler; Renata Alamino; Danielly de Paiva Magalhães; Bruna Alves Pinheiro; Mariana Vezzone; Aline Freire Serrano; Rodrigo Sardinha Lourenço; Claudio Luiz Schneider (Environmental Science and Pollution Research, 2023)

Occurrence of bean-associated cytorhabdovirus and cowpea mild mottle virus infecting cultivated and wild Passiflora spp. in Brazil - Andreza Henrique Vidal; Gustavo Pereira Felix; Emanuel Felipe Medeiros Abreu; Bruna Pinheiro-Lima; Monique Jacob Xavier Vianna; Isadora Nogueira; Ana Clara Rodrigues Abreu; Marcio Martinello Sanches; José Leonardo Santos-Jiménez; Raul Castro Carriello Rosa; Maitê Freitas Silva Vaslin; Fábio Gelape Faleiro; et al. (Crop Protection, 2023)

Medium composition and aeration to high (R,R)-2,3-butanediol and acetoin production by Paenibacillus polymyxa in fed-batch mode - Analia Borges Folle; Bruna Campos de Souza; Caroline Reginatto; Sabrina Carra; Mauricio Moura da Silveira; Eloane Malvessi; Aldo José Pinheiro Dillon (Archives of Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Occurrence of bean-associated cytorhabdovirus in soybean fields in Brazil - Bruna Pinheiro-Lima; Andreza Henrique Vidal; Dione Mendes Teixeira Alves-Freitas; Márcio Martinello Sanches; Josias Correa Faria; Cristiano Lacorte; Fernando Lucas Melo; Simone Graça Ribeiro (Crop Protection, 2023)

Growth, biofiltration and photosynthetic performance of Ulva spp. cultivated in fishpond effluents: An outdoor study - Thaís Fávero Massocato; Víctor Robles-Carnero; Bruna Rodrigues Moreira; Pablo Castro-Varela; Lorena Pinheiro-Silva; Willian da Silva Oliveira; Julia Vega; Antonio Avilés; José Bonomi-Barufi; Leonardo Rubi Rörig; Félix L. Figueroa (Frontiers in Marine Science, 2022)
Anthropogenic impacts on water resources, especially by ​​nutrient discharge, is a worldwide problem in marine coastal areas. In this context, seaweed cultivation in aquaculture wastewater can be considered as an alternative for effluent mitigation, where the biomass becomes a source of valuable compounds. The current study examined the potential use of the seaweeds Ulva pseudorotundata and Ulva rigida to remove nutrients to treat effluents from the culture of Chelon labrosus . Two experiments were conducted under pilot-scale conditions to evaluate the nutrient uptake, photosynthetic activity, and biomass production of the seaweed species cultivated under 50 and 100% effluent concentrations. Photosynthetic parameters were determined by in vivo chlorophyll a fluorescence associated to photosystem II 3 times a day to estimate photosynthetic performance and seaweed physiology throughout the experiment: optimal quantum yield ( F v /F m ), in situ and ex situ electron transport rate (ETR), photosynthetic efficiency (α ETR ), saturation irradiance ( E k ), and the maximum non-photochemical quenching (NPQ max ). To evaluate seaweed metabolism and biomass compounds, elemental and biochemical composition were analyzed in the beginning and end of each experiment. Results regarding the nutrient source showed that both species removed more than 65% of ammonium after 3 hours of experimentation. At the end of the experiments, up to 94.8% of the initial ammonium was sequestered from the effluent. Additionally, after 5 days of cultivation under 50% fish effluent both Ulva species were able to remove more than 85% of the nitrate. Although a decrease in uptake efficiency was observed in cultures with 100% fish effluent, at the end of the experiment more than 440 µmol L -1 of nitrate was removed, considering all treatment conditions. The biomass values showed that growth rates of seaweed cultivated in 100% effluent were higher than those obtained in 50% effluent. Moreover, when cultivated in the 100% effluent concentration, a significant increment in protein content was detected in both Ulva species. Our results contribute to the understanding of biofiltration and photosynthetic performance of two different Ulva species in order to improve growth optimization, enhancement of biofiltration capacity and also to boost management practices of seaweed cultivation in aquaculture effluent treatment systems.

The role of nitric oxide in renovascular hypertension: from the pathophysiology to the treatment - Bruna Pinheiro Pereira; Gabriel Tavares do Vale; Carla Speroni Ceron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Preliminary results of PBA-loaded nanoparticles development and the effect on oxidative stress and neuroinflammation in rats submitted to a chemically induced chronic model of MSUD - Caroline Paula Mescka; Daniella de Moura Coelho; Angela Sitta; Felipe Catarino; Bruna Donida; Andrea Pereira Rosa; Esteban Alberto Gonzalez; Camila Vieira Pinheiro; Fernanda Poletto; Guilherme Baldo; Carlos Severo Dutra-Filho; Carmen Regla Vargas (Metabolic Brain Disease, 2021)

Chemical composition and larvicidal activity of the essential oil from the leaves of Onychopetalum periquino (Rusby) D.M. Johnson & N.A. Murray - Bruna R. de Lima; Felipe M. A. da Silva; Elzalina R. Soares; Richardson A. de Almeida; Jessica B. Maciel; Carromberth C. Fernandes; André C. de Oliveira; Wanderli P. Tadei; Hector H. F. Koolen; Afonso D. L. de Souza; Maria L. B. Pinheiro (Natural Product Research, 2021)

Efficacy of the World Health Organization analgesic ladder in the paclitaxel-induced pain syndrome in rats - Kelly de Vargas Pinheiro; Indiara Brusco; Bruna dos Santos Hausen; Rafael Noal Moresco; Flávia K. Rigo; Sara Marchesan Oliveira; Juliano Ferreira (Inflammopharmacology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Pyrrolidine dithiocarbamate reduces alloxan-induced kidney damage by decreasing nox4, inducible nitric oxide synthase, and metalloproteinase-2 - Bruna Pinheiro Pereira; Gabriel Tavares do Valle; Bruno César Côrrea Salles; Karla Cristinne Mancini Costa; Marilene Lopes Ângelo; Larissa Helena Lobo Torres; Rômulo Dias Novaes; Sílvia Graciela Ruginsk; Carlos Renato Tirapelli; Fernanda Borges de Araújo Paula; Carla Speroni Ceron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Noninferiority field trial for evaluation of efficacy of ciprofloxacin associated with internal teat sealant as dry-off protocol - Cristian Marlon de Magalhães Rodrigues Martins; Bruna Gomes Alves; Camylla Pedrosa Monteiro; Eduardo Souza Campos Pinheiro; Marcelo Arne Feckinghaus; Luiz Gustavo Paranhos; Marcos V. dos Santos (Tropical Animal Health and Production, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Prolonged Water Deficit Reveals New Profile of Sugarcane Gene Expression and Metabolic Pathway Related to Tolerance - Bruna Robiati Telles; Flávia Maria de Souza Carvalho; Juliana da Silva Vantini; Aline Andrucioli Belesini; Giovanni Marques de Castro; Poliana Fernanda Giachetto; Samira Domingues Carlin; Thais Ramos da Silva; Daniel Guariz Pinheiro; Jairo Osvaldo Cazetta; Maria Inês Tiraboschi Ferro (Sugar Tech, 2019)

Efficient biotechnological synthesis of flavor esters using a low-cost biocatalyst with immobilized Rhizomucor miehei lipase - Ulisses M. F. de Oliveira; Leonardo J. B. Lima de Matos; Maria Cristiane M. de Souza; Bruna B. Pinheiro; José C. S. dos Santos; Luciana R. B. Gonçalves (Molecular Biology Reports, 2019)

Methylmercury Intoxication Promotes Metallothionein Response and Cell Damage in Salivary Glands of Rats - Leidiane Alencar de Oliveira Lima; Leonardo Oliveira Bittencourt; Bruna Puty; Rafael Monteiro Fernandes; Priscila Cunha Nascimento; Marcia Cristina Freitas Silva; Sérgio Melo Alves-Junior; João de Jesus Viana Pinheiro; Rafael Rodrigues Lima (Biological Trace Element Research, 2018)

Identification of compounds from Palicourea rigida leaves with topical anti-inflammatory potential using experimental models - Rafael P. Pinheiro; Muiara A. Moraes; Bruna C. S. Santos; Rodrigo L. Fabri; Glauciemar Del-Vechio-Vieira; Célia H. Yamamoto; Ana Lúcia S. M. Araújo; Aílson L. A. Araújo; Orlando V. Sousa (Inflammopharmacology, 2018)

Chemical composition and antimicrobial activity of the essential oils of Onychopetalum amazonicum R.E.Fr. - Bruna R. de Lima; Felipe M. A. da Silva; Elzalina R. Soares; Richardson A. de Almeida; Francinaldo A. da Silva Filho; Raimundo C. Pereira Junior; Álvaro J. Hernandez Tasco; Marcos J. Salvador; Hector H. F. Koolen; Afonso D. L. de Souza; Maria L. B. Pinheiro (Natural Product Research, 2016)

Chemical composition and antimicrobial evaluation of the essential oils of Bocageopsis pleiosperma Maas - Elzalina R. Soares; Felipe M.A. da Silva; Richardson A. de Almeida; Bruna R. de Lima; Hector H.F. Koolen; Caroline C. Lourenço; Marcos J. Salvador; Adriana Flach; Luiz Antonio M. A. da Costa; Antonia Q.L. de Souza; Maria L.B. Pinheiro; Afonso D.L. de Souza (Natural Product Research, 2015)

Diurnal changes in leaflet gas exchange, water status and antioxidant responses in Carapa guianensis plants under water-deficit conditions - Kaliene da Silva Carvalho; Hugo Alves Pinheiro; Reginaldo Alves Festucci-Buselli; Dalton Dias da Silva Júnior; Gledson Luiz Salgado de Castro; Flávio José Rodrigues Cruz; Bruna Sayuri Fujiyama (Acta Physiologiae Plantarum, 2013)

Further characterization of tomato-infecting begomoviruses in Brazil - Leonardo C. Albuquerque; Arvind Varsani; Fernanda R. Fernandes; Bruna Pinheiro; Darren P. Martin; Paulo de Tarso Oliveira Ferreira; Thaís Oliveira Lemos; Alice K. Inoue-Nagata (Archives of Virology, 2012)

A novel monopartite begomovirus infecting sweet potato in Brazil - Leonardo C. Albuquerque; Alice K. Inoue-Nagata; Bruna Pinheiro; Simone da G. Ribeiro; Renato O. Resende; Enrique Moriones; Jesús Navas-Castillo (Archives of Virology, 2011)